Connecting Sustainable Development with Media, Journalism and Communication Programs in European Universities - Sălcudean Minodora; Pintea Adina; Săvescu Roxana (Studies in Business and Economics, 2023)
Media plays a critical role in shaping public opinion and policy on global issues related to sustainable development. As such, journalism higher education has an important responsibility to prepare journalism students to report on sustainable development issues and to promote the Sustainable Development Goals. However, integrating the SDGs into journalism curricula presents several challenges. This article reviews the current state of teaching the SDGs in European journalism higher education and identifies the challenges and opportunities for integrating the SDGs into journalism curricula. The authors examine the connection between journalism programs, courses and the topics of the SDGs, in the European university environment by accessing existing reports (mainly from institutions like UN, UNESCO, EU-HEIs), studies and articles on SDGs in journalism and the websites of EU-HEIs. The EU universities providing Journalism / Media Programs were selected based on three criteria: i/ the 2020 QS World University Ranking by Subject (subjects used: “communication & media studies”, “development studies”), ii/ Google search based on keywords related to journalism or media education and SDGs and iii/ existing partnerships LBUS has with European universities in the field of journalism and media.